2007
DOI: 10.1104/pp.107.099820
|View full text |Cite
|
Sign up to set email alerts
|

A Reassessment of the Function of the So-Called Compatible Solutes in the Halophytic Plumbaginaceae Limonium latifolium  

Abstract: The compatible solute hypothesis posits that maintaining osmotic equilibrium under conditions of high salinity requires synthesis of organic compounds, uptake of potassium ions, and partial exclusion of NaCl. To assess whether osmotic adaptation in Limonium latifolium proceeds according to this hypothesis, a comprehensive analysis of solute accumulation during NaCl treatments was conducted. Determination of prevailing inorganic ions and establishment of the metabolic profiles for low M r organic substances rev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
108
1
2

Year Published

2010
2010
2024
2024

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 163 publications
(118 citation statements)
references
References 65 publications
7
108
1
2
Order By: Relevance
“…Conversely, NaCl-treated L. latifolium plants accumulated less Na in their shoots at equivalent salinity levels. This result suggested that this plant possesses a better capacity to control the absorption of sodium ions and/or the excretion of such ions through its leaves, probably in relation to its high capacity to accumulate osmoregulatory solutes (Gagneul et al 2007). In addition, we observed the presence of salt crystals on both sides of L. latifolium leaves, proportionally to the salinity concentrations in the medium (data not shown).…”
Section: Discussionmentioning
confidence: 98%
“…Conversely, NaCl-treated L. latifolium plants accumulated less Na in their shoots at equivalent salinity levels. This result suggested that this plant possesses a better capacity to control the absorption of sodium ions and/or the excretion of such ions through its leaves, probably in relation to its high capacity to accumulate osmoregulatory solutes (Gagneul et al 2007). In addition, we observed the presence of salt crystals on both sides of L. latifolium leaves, proportionally to the salinity concentrations in the medium (data not shown).…”
Section: Discussionmentioning
confidence: 98%
“…Also, field studies revealed only small fluctuations in GB contents in response to drastic changes in environmental conditions (i.e., in soil humidity and salinity) in some halophytes that use GB as the functional osmolyte [36]. These data suggest the existence of constitutive mechanisms of tolerance in plants adapted to stressful environments, based on changes in the intracellular location of specific osmolytes rather than on their de novo synthesis [79], and similar mechanisms could also operate in L. decidua.…”
Section: Osmolyte Synthesismentioning
confidence: 91%
“…Similarly, the accumulation and maintenance of a high sugar pool containing nonreducing sugars and oligosaccharides has been reported to act as a replacement for water by providing a hydration shell around proteins. Although there is evidence from some previous studies that enhanced accumulation of Pro (Hong et al, 2000) and sugars (Hoekstra et al, 2001;Bogdan and Zagdanska, 2006;Urano et al, 2009) improves the osmotic stress tolerance of plants, there have also been reports that the accumulation of organic compatible solutes makes only minor contributions to osmotic stress tolerance (Gagneul et al, 2007;Hill et al, 2013). Here, metabolites of Glu and Pro metabolism (including Gln, Orn, Arg, and 5-oxo-Pro) and sugar metabolism (raffinose, Fru, and Glc) were highly genetically correlated with grain yield and other yield-related agronomic traits.…”
Section: Correlated Responsesmentioning
confidence: 99%